MONITORING OF ANTIMICROBIAL RESISTANCE OF AVIBACTERIUM (HAEMOPHILUS) PARAGALLINARUM ISOLATES RECOVERED IN THE TERRITORY OF THE RUSSIAN FEDERATION AND THE REPUBLIC OF BELARUS IN 2015 - V. A. Danilova; A. V. Potekhin; I. A. Stepanova (Ветеринария сегодня)
Monitoring of antibacterial resistance of 9 infectious Coryza (Haemophilus infection) isolates recovered in the territory of the Russian Federation and the Republic of Belarus in 2015 was performed. Most of the isolates were sensitive to aminopenicillins (55.5%), III-IV generation cephalosporins (100%), and florfenicol (100%). Most of the isolates were resistant to gentamycine, erythromycin, chlortetracycline and sulfamethoxazole with trimethoprim. All isolates demonstrated resistance to tilmicosin, oxytetracycline, doxycycline, lincomycin and neomycin.